PENERAPAN KONSELING BEHAVIORAL ANAK TUNAGRAHITA UNTUK MENINGKATKAN KEPERCAYAAN DIRI - Solehan Muzaqi; Haryu Islamudin (UIN Kiai Haji Achmad Siddiq Jember, 2021)
Mental retardation is a child who experiences different intellectual abilities from children in general. This makes it difficult for mentally retarded children to communicate between peers and makes the self-confidence of mentally retarded children disappear. Therefore, SLB teachers strive to increase self-confidence in mentally retarded children. Based on this phenomenon, it is a priority for teachers at SLB PGRI Bangorejo in increasing self-confidence. This study aims to describe the application of behavioral counseling for mentally retarded children to increase self-confidence in SLB PGRI Bangorejo. This research uses a qualitative approach and the type of research is File Research. Data collection: observations, interviews and documentation. Data analysis: data reduction, data presentation and conclusions. This study found the following conclusions: the behavioral counseling process at SLB PGRI Bangorejo the accompanying teacher there carried out several steps such as (1) assessment, (2) determining goals, and (3) evaluation. understand the characteristics of each student, build empathy for the counselee, persuade the counselee to feel comfortable with the counselor, provide understanding and advice. The results achieved are being able to read the alphabet in front of the class and then there are also creative students (counting themselves, drawing by themselves, and separating colors correctly).